2015
DOI: 10.1093/bja/aev229
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based therapy for traumatic brain injury

Abstract: Traumatic brain injury is a major economic burden to hospitals in terms of emergency department visits, hospitalizations, and utilization of intensive care units. Current guidelines for the management of severe traumatic brain injuries are primarily supportive, with an emphasis on surveillance (i.e. intracranial pressure) and preventive measures to reduce morbidity and mortality. There are no direct effective therapies available. Over the last fifteen years, pre-clinical studies in regenerative medicine utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 90 publications
1
58
0
6
Order By: Relevance
“…It has been revealed that enhancing neurogenesis, angiogenesis, and immunoregulation by secreting chemokine and growth factors are involved in the functional recovery induced by stem cell/progenitor cellbased interventions. [96][97][98][99] Several clinical trials in cell-based treatment for TBI recovery have demonstrated safety of this therapeutic approach. 100,101 However, the administration route, dose, and time window still remain controversial.…”
Section: Neurorestorationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been revealed that enhancing neurogenesis, angiogenesis, and immunoregulation by secreting chemokine and growth factors are involved in the functional recovery induced by stem cell/progenitor cellbased interventions. [96][97][98][99] Several clinical trials in cell-based treatment for TBI recovery have demonstrated safety of this therapeutic approach. 100,101 However, the administration route, dose, and time window still remain controversial.…”
Section: Neurorestorationmentioning
confidence: 99%
“…99,101,102 The administration dose of MSCs ranges from 0.1 to 20 million cells per kg body weight. 96 The approaches of lateral ventricle and intravenous injection have been utilized. 96 The timing for MSC transplantation in experimental animal models has been intensively studied within 24 h after TBI.…”
Section: Neurorestorationmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[23][24][25] Several preclinical studies have evaluated the efficacy of rodent neural precursor cells in TBI rodent models. 22,[26][27][28][29][30] The culturing NSCs in vitro started as an attempt to grow multipotent embryonic cortical tissue (the word neural stem cells was not yet coined) and successfully accomplished in 1989 at the University of Miami. 31 This work evolved when Martin Raff, a Canadian born Boston neurologist decided to move to England and chose to leave the United States (US) than fight in Vietnam War and to pursue immunology.…”
Section: Step 1 Cell Therapy Candidatementioning
confidence: 99%
“…To this end, there is a strong interest in the potential of cell transplantation. 2,3 Among the cell populations currently available, human mesenchymal stem cells (hMSCs), derived from bone marrow, seem to have definite therapeutic potential due to their low immunogenicity under either autologous or allogeneic conditions, [3][4][5] although potential complications including cell clotting and cell-induced microembolism might impair their therapeutic safety and efficacy. 6 Their responses to the particular pathological microenvironments of cerebral ischemia make hMSCs exert multiple therapeutic effects at various sites and times within the stroke lesion by preventing neural cell death and improving neurological function.…”
Section: Introductionmentioning
confidence: 99%